PENGARUH PENERAPAN PEMBELAJARAN ONLINE TERHADAP HASIL BELAJAR MELALUI MINAT BELAJAR PADA MATA PELAJARAN MARKETING KELAS X (SEPULUH) KOMPETENSI DASAR 3.9 DI SMK KETINTANG SURABAYA - Hervina Dwi Septorini; Harti Harti (Fakultas Ekonomi Universitas Negeri Medan, 2021)
The research was conducted to determine whether online learning affects learning outcomes through learning interest in marketing subjects for class X KD. 3.9 about analyzing the product life cycle at SMK Ketintang Surabaya. The sample is the tenth grade students of SMK Ketintang Surabaya, the online business and marketing expertise program, totaling 68 students. This research is a type of quantitative research. Collecting data using a closed Likert scale questionnaire. Data were analyzed by path analysis technique. The results of the study explain that online learning has a significant influence on learning interest by 21,6%, learning interest has a significant influence on learning outcomes by 39%, online learning has a direct influence on learning outcomes by 39%, and online learning on learning outcomes through interest in learning does not have a significant effect because the direct influence value is greater than the indirect influence value, namely 45,6% > 10,5%. It is hoped that this research will provide benefits for a teacher to know what can affect student learning outcomes.